The Influence of Tourist Attractions Towards the Tourists’ Satisfaction - Kirom, N R; ., Sudarmiatin; Adi Putra, I Wayan Jaman (KnE Social Sciences, 2018)
A tourism object is a form of a facility, which can attract tourists or visitors to come to a certain area or place. It is also identical to an act of someone going to a place. According to Act No 10 the year 2009, tourism is a natural condition, flora, and fauna, as a gift from God, as well as ancient relics, historical relics, arts, and cultures owned by Indonesia as a resource and tourism capital development needed to push the equality of having the entrepreneurship opportunities and acquiring benefits as well as confronting challenges of local, national, and global changes. This research aims to understand the influence of culture towards the tourists’ satisfaction on cultural-related tourism objects in the Regency area of Malang, East Java, Indonesia. The sample of this research is the tourists who come to Islamic Boarding School Biharu Bahri Asali Fadhoilir Rohmah. This is an ex-post facto research with quantitative data. The result of this research shows that culture affects positively and significantly towards the tourists’ satisfaction. Keywords: culture, tourism objects, tourists